Common fixed point theorems for geraghty’s type contraction mapping with two generalized metrics endowed with a directed graph in JS-metric spaces - Phakdi Charoensawan (2018)
© 2018, SINUS Association. All rights reserved. The purpose of this work is to present some existence results for common fixed point theorems for Geraghty contraction mappings with two generalized metrics endowed with a directed graph in JS-metric spaces. Some examples supported our main results are also presented.